Carmel Mission. - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows the Mission San Carlos Borromeo de Carmelo, also known as the Carmel Mission. This Mission is a historic Roman Catholic mission church in Carmel, California. It was destroyed in the mid 1800s, only to be restored beginning in 1884. Mission Carmel has been designated a National Historic Landmark by the National Park Service. It is also an active parish church of the Roman Catholic Diocese of Monterey and is the only one to have its original bell tower dome.